Biography pages of Juozas Albinas Lukša-Daumantas 1940–1941 - Rukšėnas, Alfredas (Genocidas ir rezistencija, 2020)
The article examines some pages of the life history of the famous post-war partisan Juozas Albinas Lukša Daumantas (10 August 1921 – 4 September 1951) from 1940 through 1941 that have so far received little attention. One of the tasks of the paper is to reveal the role of Lukša in the Lithuanian anti-Soviet resistance movement. It is claimed that three periods of Lukša’s resistance activity to the Soviet regime in 1940–1941can be relatively distinguished. The first period covers the period from the occupation of Lithuania carried out by the Soviet Union on 15 June 1940 (on the same day Lukša was issued a certificate of graduation from a gymnasium) to the 28th of August of the same year, i. e. before his admission to the Faculty of Construction of Kaunas Vytautas Magnus University. At that time, a resistance motivation formed, which encouraged Lukša to oppose the Soviet regime and seek the restoration of independent Lithuania. However, there is no specific data on his resistance during this period. Relatively, it can only be said that Lukša became a member of the anti-Soviet underground movement already on 15 June 1940. Such an assessment is possible due to the fact that before the occupation and annexation of Lithuania in the summer of 1940, Lukša was a member of the Lithuanian Catholic Federation “Ateitis”, which was banned and operated illegally during the reign of President Antanas Smetona. During the Soviet era, the activity of this organization was not legalized, and the organisation operated informally. The second period covers the period from the admission to the University (28 August 1940) to 4 March 1941. After starting his studies, Lukša joined the organisation “Grandis”, an illegally-operating corporation of the Lithuanian Catholic Federation “Ateitis”, which, like other student corporations, was banned by the Soviet regime. This organization, in turn, was a member of the illegal Student Coalition, chaired by a member of “Ateitis”, Pilypas NarutisŽukauskas. This accession also meant the transition of Lukša from an illegal pupil organization belonging “Ateitis” to an illegal student organization of “Ateitis”. Although there is no specific information about Lukša’s activities during the aforesaid period, the case may be that Lukša had one or another relationship with the anti-Soviet resistance activities of Kaunas Vytautas Magnus University’ students, as evidenced by historical literature and sources. The existence of this relationship was possible since the mentioned students together with Lukša studied in the same educational institution, were people from the same environment were present. The third period covers the period from 4 March 1941 until Lukša’s arrest on the 6th of June of the same year. It should be mentioned that on the 4th of March, Lukša, a member of the illegal corporation “Grandis”, which in turn was a member of the illegal Student Coalition, took an oath and joined the Lithuanian Activist Front (LAF). This step was partly influenced by the fact that the illegal Student Coalition, a member “Ateitis”, already in December of 1940 decided to unite for the fight for independence under the umbrella of the Lithuanian Activist Front (LAF). On the day of taking the oath, Lukša was probably already a member of the five-person group led by Kazimieras Gediminas Ruzgys. The five-person group itself probably already existed before the 4th of March and was part of the broad anti-Soviet underground movement. The members of the five-person group were connected through intermediaries with the Kaunas LAF headquarters, which was headed by Pilypas Narutis-Žukauskas, the chairman of the illegal Student Coalition and a member of “Ateitis”. Although the activities of Lukša and the other five members of the fiveperson group were multidisciplinary, they were mainly related to the dissemination of anti-Soviet literature. Some of the literature contained statements directed against the Jews; however, it is not known that Lukša or the other five members of the five-person group made such statements. As a result, it cannot be said that they were anti-Semites. On the other hand, there were other statements besides anti-Semitic ones. The resistance activities of the five-person group ceased in June of 1941 when Soviet Lithuanian security officials arrested Juozas Albinas Lukša, Bronius Barzdžiukas, Bronius Vaidila, Kazys Gediminas Ruzgys. They were detained in the Prison no. 1 of the People’s Commissariat for Internal Affairs (Народный комиссариат внутренних дел: Narodnyy Komissariat Vnutrennikh Del; abbreviated NKVD). The security forces who carried out the prosecution included some Jews as well. When the war broke out, the arrested members of the five-person group were released from prison, and Bronius Barzdžiukas and Kazys Gediminas Ruzgys took part in the June uprising. The opinion formed by individual members of society (probably unintentionally) that Lukša was close to the fascist worldview is not correct. This is possible due to the fact that Lukša was related to the other members of the five-person group by the relationship maintained through the intermediaries through the Kaunas LAF headquarters, which was headed by Pilypas Narutis-Žukauskas. Kaunas LAF (as well as Vilnius LAF) did not prepare and was not interested in preparing platform documents of a different nature, in which the statements contained would allow seeing the signs of a fascist organization. This was probably influenced by the fact that it was operating in Soviet-occupied Lithuania, and that the Nazi regime could not directly influence its activities. These documents are found only in the activities of the LAF in Berlin, which could hardly have escaped the Nazi’s influence. On the other hand, for the members of the Kaunas LAF headquarters, not everything was acceptable in the activities of the Berlin LAF, and they did not want its proclamations and considered it to be a completely different organization. This opinion is not correct also because the Kaunas LAF organization (as well as the Vilnius and Berlin LAF organizations) consisted of people with different views, rather than a unified group of members, all of whom were loyal to the fascist doctrine. Lukša cannot be considered a fascist, since he was not among the Voldemarians (voldemarininkai), who separated from the LAF and became members of the Lithuanian Nationalist Party (LNP), which was hostile to the LAF. He cannot be considered to be a fascist because after the Nazis banned the activities of the LAF and the LNP, Lukša chose to become a member of the Lithuanian Nationalist Party (LNP), hostile to the LAF. Lukša chose membership in the underground anti-Nazi organization the Lithuanian Front (it consisted mostly of the members of the Lithuanian Christian Democratic Party, members of “Ateitis”, etc.) and not in the Union of Lithuanian Freedom Fighters which gathered the Voldemarians and the members of the LNP. The task of the paper is to find out whether the statements of Jewish researchers that Juozas Albinas Lukša was a participant of the massacre that took place in the garage of the Lithuanian Union of Agricultural Cooperatives “Lietūkis” in Kaunas on 27 June 1941 are correct. It is stated that the statements of the Jewish researchers Joseph A. Melamed, Joseph Zak, Abraham Lewin, Alex Faitelson who claimed Juozas Albinas Lukša participated in the massacre of Jews in the garage of Lietūkis in Kaunas on 27 June 1941 cannot be considered correct because they are not based on the testimony provided by immediate witnesses. Although Faitelson named Jonas Barškėtis as an immediate witness, this was not the case. Primarily it was due to the fact that Jonas Barškėtis was arrested in Kaunas by partisans before the massacre in the garage, i. e. on 25 June 1941. He was not released until 30 July 1941. Secondly, Faitelson based his statements about Barškėtis as an immediate witness by distorting the memories of Nachman Dushanski. Although Dushanski described Lukša as a participant in the massacre in the garage, however, he did not name Barškėtis, whom he knew very well, as a person who was a witness to the massacre. According to his recollections, Lukša was recognized as a murderer by some other person than his good acquaintance Barškėtis. On the other hand, Dushanski did not name in his memoirs any immediate witness who would have seen Lukša in the garage. He probably did not know such witnesses himself but relied on some secondary, unreliable sources. Joseph A. Melamed, Joseph Zak, and Abraham Lewin claimed that Lukša can be seen in two surviving photos of the massacre of Jews in the garage of “Lietūkis”. These allegations are questionable because the photographs are of a relatively poor quality and the identification of the person holding a crowbar in his hands has not been carried out by competent specialists (at least the author of the paper has no knowledge of this). They probably formed the version of Lukša being seen in the photos on the basis of Dushanski’s memoirs, in which Lukša is named as a participant of the massacre in the garage without the testimony of immediate witnesses but instead on the basis of secondary and unreliable sources. The statements made by the Jewish researchers that Lukša participated in the massacre of Jews in the garage of Lietūkis in Kaunas on 27 June 1941 cannot be considered true not only because of the lack of information received from immediate witnesses but also because there were some witnesses who saw with their own eyes what Lukša was doing after being released from prison. According to their information, left Lukša to Juodbūdis village (Marijampolė district, Veiveriai county) already on 23 June 1941.